Comrades in the Family? Soviet Communism and Informal Family Insurance - Joan Costa-Font; Anna Nicinska (Institute of Labor Economics (IZA), 2020)
We study the effect of exposure to communism (EC), a political-economic regime based on collectivist planning, on preferences for family supports, which we refer to as 'informal family insurance'. We exploit both cross-country and cohort variation in EC in a large sample of Central and Eastern European countries (CEEC). Against the backdrop that 'communism gives rise to the abolition of the family', we find robust evidence that EC strengthens the preference for family insurance which coexists with a stronger preference for social insurance. We find a six per cent increase in preferences for care to older parents and a four per cent increase in preferences for support to pre-school children and financial support to adult children. These effects are explained by the erosion of both generalized trust and the lower confidence in public institutions, suggesting that (raising uncertainty and adversity during) communism increased the demand for all types of available insurance.
Keywords: Z1; P3; 330; informal family insurance; family networks; social insurance; interpersonal trust; confidence in institutions; Soviet communism; Eastern Europe